Flow pattern analysis in a rotating scraped surface plate heat exchanger. (September 2019) - Martínez, D.S.; Solano, J.P.; Vicente, P.G.; Viedma, A.
Highlights: Mean velocity field in a scraped surface plate heat exchanger is obtained through PIV. Three different flow regions in the top, front and rear side of the blades are identified. Influence of rotational Reynolds number on upwards and downwards flow is described. The role of the operational parameters on mixing is assessed. URANS numerical modelling allows to address the effect of centrifugal forces and strong radial flow. Abstract: The flow pattern inside a scraped surface plate heat exchanger used for ice slurry production is studied both experimentally and numerically. Isothermal planar velocity fields are reported in the range 2.2 · 10 4 ⩽ Re rot ⩽1.7 · 10 5 using a phase averaged PIV technique. Unsteady RANS modelling of the flow, using the rotating frame methodology is used to obtain a time-averaged description of the flow structure, which was successfully validated against the PIV data. The flow structure is characterized by the presence of a roll-up vortex generated by the scraper blade, which is the main factor for both the radial and vertical displacements of the flow. Increasing the Re rot number leads to a more uniform flow, reducing the presence of stagnant zones. However, the main pattern structure does not change significantly when increasing the scraping velocity.